Short- and long-term follow-up and additional benefits in a sickle cell disease patient experienced severe crizanlizumab infusion-related vaso-occlusive crisis: A case report - Alshurafa, Awni; Yassin, Mohamed A. (Frontiers in Medicine, 2022)
Sickle cell disease is an autosomal recessive disorder characterized by the presence of sickle hemoglobin which leads to chronic hemolysis, and vaso-occlusive crisis. After decades of limited therapy options, crizanlizumab is a humanized monoclonal antibody approved by the Food and Drug Administration (FDA) in 2019 for sickle cell-related pain crises for patients 16 years of age and above. Although rare, infusion-related reactions, including painful crises, occurred in 3% as per the package insert. However, the data on how to deal with such reactions and about further treatment outcomes are limited as most patients stopped crizanlizumab after the reaction. Herein, we report the good outcome of 13 doses of crizanlizumab in a 19-year-old female patient with sickle cell disease on hydroxyurea, despite experiencing a severe infusion-related painful crisis during the second infusion. Additional benefits of crizanlizumab, in this case, were preventing new episodes of acute chest syndrome, quitting chronic narcotics use, and a remarkable improvement in quality of life and overall performance.